Analysis of Reverse Logistics Management in China - Zhu, Xiaoqi (2007)
With the global market competition becoming fierce, there is increasing concern regarding sustainable development strategy. The notion of sustainable development makes reverse logistics recognized. Reverse Logistics has recently received growing attention all over the world, and many enterprises have begun to regard it as a streamlined business strategy to gain economic benefits and maximize recovery value, to reduce waste and minimize cost, and to improve the corporate image and increase market share. While most local Chinese enterprises are familiar with forward logistics activities, the notion of reverse logistics is relatively new for many Chinese companies currently, or it is simply regarded as waste management. Although the related research on China's reverse logistics management is in infancy, it has become a crucial research topic in the current sustainable economy strategy development in China.